PENGARUH MEDIA BOLA GANTUNG TERHADAP MOTIVASI BELAJAR PASSING BAWAH BOLA VOLI SMAN 4 SUNGAI RAYA - Sulistiyono, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractHis study aims to determine the effect of hanging ball media on passing motivation under volleyball student grade X SMA Negeri 4 Sungai Raya. The method of this research is experimental method with the form of pretend experiment research (Quasy experiment). The sample of this study is students of SMA Negeri 4 Sungai Raya, which amounts to 68 people who are divided into two classes. The data were collected by purposive sampling technique. The existence of hanging ball media in an effort to increase motivation to learn there is an increase of 48% and has a level of interprestasi media correlation of the ball hanging with learning motivation with strong criteria. In addition, there is also the influence of hanging media to the motivation of learning of class X students in passing under volleyball in SMA Negeri 4 Sungai Raya with rxy value (ie = 0.69) ranging from 0.600 to 0.799 means including a strong positive correlation. With df of 32, at 5% significance level obtained r table value = 0.349 and r count of 0.69. So, the results of this study can be concluded that there is influence of hanging ball media to motivation learn. Keywords : Hanging Ball, and Passing Under Volleyball Motivation